Quantitative Activity Measurements of Brown Adipose Tissue at 7 T Magnetic Resonance Imaging After Application of Triglyceride-Rich Lipoprotein 59Fe-Superparamagnetic Iron Oxide Nanoparticle: Intravenous Versus Intraperitoneal Approach. Issue 3 (March 2016) - Jung, Caroline Sophie Laura; Heine, Markus; Freund, Barbara; Reimer, Rudolph; Koziolek, Eva Jolanthe; Kaul, Michael Gerhard; Kording, Fabian; Schumacher, Udo; Weller, Horst; Nielsen, Peter; Adam, Gerhard; Heeren, Jörg; et al.
Abstract : Objectives: The aim of this study was to determine metabolic activity of brown adipose tissue (BAT) with in vivo magnetic resonance imaging (MRI) after intravenous (IV) and intraperitoneal (IP) injection of radioactively labeled superparamagnetic iron oxide nanoparticles (SPIOs) embedded into a lipoprotein layer. Materials and Methods: 59 Fe-labeled SPIOs were either polymer-coated or embedded into the lipid core of triglyceride-rich lipoproteins (TRL- 59 Fe-SPIOs). First biodistribution and blood half time analysis in thermoneutral mice after IP injection of either TRL- 59 Fe-SPIOs or polymer-coated 59 Fe-SPIOs (n = 3) were performed. In the next step, cold-exposed (24 hours), BAT-activated mice (n = 10), and control thermoneutral mice (n = 10) were starved for 4 hours before IP (n = 10) or IV (n = 10) injection of TRL- 59 Fe-SPIOs. In vivo MRI was performed before and 24 hours after the application of the particles at a 7 T small animal MRI scanner using a T2*-weighted multiecho gradient echo sequence. R2* and ΔR2* were estimated in the liver, BAT, and muscle. The biodistribution of polymer-coated 59 Fe-SPIOs and TRL- 59 Fe-SPIOs was analyzed ex vivo using a sensitive, large-volume Hamburg whole-body radioactive counter. The amount of 59 Fe-SPIOs in the liver, BAT, and muscle was correlated with the MRI measurements using the Pearson correlation coefficient. Tissue uptake of 59 Fe-SPIOs was confirmed by histological and transmission electron microscopy analyses. Results: Triglyceride-rich lipoprotein 59 Fe-SPIOs exhibited a higher blood concentration after IP injection (10.1% ± 0.91% after 24 hours) and a greater [INCREMENT]R2* in the liver (103 ± 5.0 s −1 ), while polymer-coated SPIOs did not increase substantially in the blood stream (0.19% ± 0.01% after 24 hours; P < 0.001) and the liver (57 ± 4.08 s −1 ; P < 0.001). In BAT activity studies, significantly higher uptake of TRL- 59 Fe-SPIOs was detected in the BAT of cold-exposed mice, with [INCREMENT]R2* of 107 ± 5.5 s −1 after IV application (control mice: [INCREMENT]R2* of 22 ± 5.8 s −1 ; P < 0.001) and 45 ± 5.5 s −1 after IP application (control mice: [INCREMENT]R2* of 11 ± 2.9 s −1 ; P < 0.01). 59 Fe radioactivity measurements and [INCREMENT]R2* values correlated strongly in BAT ( r > 0.85; P < 0.001) and liver tissue ( r > 0.85; P < 0.001). Histological and transmission electron microscopy analyses confirmed the uptake of TRL- 59 Fe-SPIOs within the liver and BAT for both application approaches. Conclusions: Triglyceride-rich lipoprotein–embedded SPIOs were able to escape the abdominal cavity barrier, whereas polymer-coated SPIOs did not increase substantially in the blood stream. Brown adipose tissue activity can be determined via MRI using TRL- 59 Fe-SPIOs. The quantification of [INCREMENT]R2* using TRL- 59 Fe-SPIOs is feasible and may serve as a noninvasive tool for the quantitative estimation of BAT activity. Abstract : Supplemental digital content is available in the text.